2010
DOI: 10.1002/chem.201000176
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Colorimetric Identification and Targeted Photothermal Lysis of Salmonella Bacteria by Using Bioconjugated Oval‐Shaped Gold Nanoparticles

Abstract: Salmonella bacteria are the major cause for the infection of 16 million people worldwide with typhoid fever each year. Antibiotic-resistant Salmonella strains have been isolated from various food products. As a result, the development of ultrasensitive sensing technology for detection and new approaches for the treatment of infectious bacterial pathogens that do not rely on traditional therapeutic regimes is very urgent for public health, food safety, and the world economy. Driven by this need, we report herei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(107 citation statements)
references
References 44 publications
3
104
0
Order By: Relevance
“…Photo-excitation of gold nanostructures at their LSPR band can efficiently convert photon energy into heat and can be used for the photothermal ablation of cancer cells. Unlike spherical nanoparticles, which absorb light in the visible region, [13][14][15][16][17] gold nanorods (Au NRs) shift the excitation wavelength to the near-infrared region (NIR). 18 The flexibility in tuning the longitudinal plasmon band to the NIR makes them attractive for in vivo biomedical detection and therapy, as light in the NIR region can deeply penetrate into tissue without significant absorption and heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…Photo-excitation of gold nanostructures at their LSPR band can efficiently convert photon energy into heat and can be used for the photothermal ablation of cancer cells. Unlike spherical nanoparticles, which absorb light in the visible region, [13][14][15][16][17] gold nanorods (Au NRs) shift the excitation wavelength to the near-infrared region (NIR). 18 The flexibility in tuning the longitudinal plasmon band to the NIR makes them attractive for in vivo biomedical detection and therapy, as light in the NIR region can deeply penetrate into tissue without significant absorption and heat generation.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms of pulsed laser-induced photothermal damage to bacteria may involve generation of acoustic and shock waves, bubble formation, thermal injury, and melting or fragmentation of the nanoparticles. 10,18,19 Not all of the bacteria showed overt signs of damage after laser exposure, including some that had nanoparticles attached to the surface. It is possible that the typical growth pattern of S. aureus as clumps may shield some of the bacteria from the incident laser energy or binding of a sufficient number of GNPs to induce complete killing.…”
Section: Resultsmentioning
confidence: 99%
“…16 Previous studies have shown that use of GNPs with continuous wave or pulsed laser irradiation can significantly decrease the viability of several types of bacteria via photothermal cell lysis. [9][10][11][12]17,18 Zharov et al 10 proposed that the precision of microbial killing could be maximized and collateral host tissue damage minimized by combining nanomaterials functionalized with antibodies against specific bacterial cell wall components and nanosecond pulsed laser exposure. The antibody increases the specificity of nanoparticle binding, thereby targeting the thermally induced damage to the vicinity of the bacterial surface.…”
mentioning
confidence: 99%
“…The limit of detection for the color change with the naked eye was 10 cfu mL À1 , which is one order higher than the result in Fig. 4 and two orders of magnitudes higher than that of the competing technologies [26][27][28]. The concentration of E. coli in each solution was determined quantitatively using a portable UV-vis spectrometer by measuring the light absorption intensity at 368 nm; the absorption peak intensity of the sample increased with E. coli concentration (Fig.…”
Section: Detection Of E Coli Using the Catalytic Oxidation Of Tmbmentioning
confidence: 82%